Biodiversity protection in Malaysia: a legal perspective - Mustafa, Maizatun (2018)
Malaysia is a rich country in term of biodiversity and hosts one of the oldest rainforests in the world. However, the past few decades have seen the loss of Malaysia’s biodiversity and reduction of forest cover due to economic development and overexploitation of natural resources. At the same time, advancement in technology and expansion in global trade also pose possible threats to biodiversity in terms of unlawful access or misuse. Until now, Malaysia’s commitment towards biodiversity protection is evident through the passing of a number of related legislations and ratification of international conventions. The objectives of this presentation are to highlight existing policy and law on biodiversity and to address some fundamental aspects of biodiversity protection, including the sovereign rights of countries to control the use of their biological resources, and to regulate access to, and compensate for, the use of such resources. The presentation also seeks to reveal the complexity of biodiversity management from the perspective of legal framework creating possible constraints and inadequacies in effective management of aspects of biodiversity.